Social Network Sites, Individual Social Capital and Happiness - Efstratia Arampatzi; Martijn J. Burger; Natallia A. Novik (Tinbergen Institute, 2016)
Can online social contacts replace the importance of real-life social connections in our pursuit of happiness? With the growing use of social network sites (SNSs), attention has been increasingly drawn to this topic. Our study empirically examines the effect of SNS use on happiness for different subgroups of young adults. More specifically, we examine whether the effect of SNSs on happiness is moderated by individual social capital, as measured in terms of frequency of social contacts and feelings of loneliness. Using Dutch data from the Longitudinal Internet Studies for the Social Sciences (LISS panel), we provide robust empirical evidence that there is, on average, no relationship between the amount of time spent on SNSs and happiness. However, we find a negative association between the numbers of hours spent on SNS and happiness for SNS users who feel socially disconnected and lonely. The results hold when we control for socio-demographic characteristics, trust, hours spent on other Internet sites and household income. Hence, SNSs are not a substitute for real-life social connections and, at most, complement them.
Keywords: I31; L86; Z13; 330; Subjective well-being; happiness; social network sites; individual social capital; social isolation; loneliness